Gerakan Penanaman Tanaman Obat Keluarga (TOGA) dalam Pengoptimalan Lahan Pekarangan Untuk Peningkatan Kesehatan Masyarakat Dusun Jurang - Mariska Pratiwi; Heni Silvia; Susi Ratna Sari; Icha Bella; Amelia Agista Putri; Siti Nurul Iftitah (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2025)
Jurang Hamlet is one of the hamlets located in Girirejo Village, Tempuran District, Magelang Regency. In general, people in Jurang Hamlet have a fairly large yard land. The land can be used and optimized, one of which is by planting family medicinal plants (TOGA). TOGA is a plant that is usually used as a traditional medicine to treat various diseases and is usually grown in the yard of the house. There are problems that occur in Jurang Hamlet, namely the lack of understanding and knowledge related to the planting and utilization of TOGA. In addition to increasing public knowledge and understanding, this activity is also intended to empower the PKK women of Jurang Hamlet in terms of managing medicinal plants in the yard of the house. This community empowerment activity uses three methods: (1) Preparation of TOGA seeds, (2) Socialization of effective TOGA planting methods, (3) Socialization of the benefits of each TOGA to be planted, (4) The distribution of TOGA seedlings and the planting of TOGA together. From the results of the TOGA planting activities that have been carried out by the residents of Jurang Hamlet, it is known that the residents of Jurang Hamlet have become more aware of how to plant TOGA well and also some of the benefits of each plant seed that has been distributed.